The services of Ziri Ibn Manad Sanhaji and his role in the defense of the Fatimid Obeidia state in the Maghreb (324 AH-360 H / 935 AD-971 AD) - ben zaoui, tarek (Journal of Social Sciences and Humanities, 2019)
Since the 2nd century AH, the Maghreb has experienced many conflicts that led to continuous wars, and the results were the emergence of many contradictory entities in their political and doctrinal orientation, and among the most important of these entities and the most powerful Fatimid state founded by Shiite preacher Abu Abdullah al-Sanaani, relying on the barbaric tribe Kutama, who suffered the greatest plague, and with the unexpected end of the state's founder, Abu Abdullah al -Shi'a, also the emergence of new tribal and regional variables, the Fatimid caliphs understood that the search for a strong ally who had not yet been weakened by the wars became urgent, That's what they found in the Sanhaja tribe, which became by the direction of Ziri IBn Manad, a rising force in the region, and the leader of Sanhaji did not hesitate to announce his allegiance to the Fatimids by offering them great services, and was not in his loyalty to them less than the sincerity of the Kittamites, and this is what strengthened the relationship between the two parties and had a great impact on the continued presence of the Fatimids in the Maghreb.